Thermodynamic analysis of absorption refrigeration cycles by parabolic trough collectors - Albaker, Abdullah (2023)
“The purpose of this study is to numerically investigate the performance of a solar physical surface absorption cooling system, in which activated carbon/methanol is used as a working pair, which is placed inside a parabolic-shaped solar collector. The governing mathematical model of this issue is based on the equations of conservation of mass, conservation of energy, and thermodynamics of the physical surface absorption process. The equations are discretized using the fully implicit finite difference method, and the Fortran computer program was simulated. A comparison with the results of previous laboratory and numerical studies validated this model. At each point in the bed, the temperature, pressure, and mass of the refrigerant absorbed during the physical surface absorption/discharge process were calculated. In addition, the effects of the bed diameter, amount of solar radiation, source temperature, temperature, and pressure of the evaporator and condenser were investigated on the solar performance coefficient and the specific cooling power of the system. According to the built laboratory model and the working conditions of the system, the solar performance coefficient and the specific cooling capacity of the system are equal to 0.12 and 45.6 W/kg, respectively.“